2021
DOI: 10.36974/jbi.v12i1.6509
|View full text |Cite
|
Sign up to set email alerts
|

KOMPOSISI KIMIA DAN UJI AKTIVITAS ANTIBAKTERI MINYAK ATSIRI DAUN KAYU PUTIH (Melaleuca cajuputi) DARI KOTA SINGKAWANG

Abstract: ABSTRAK. Kayu putih (Melaleuca cajuputi) merupakan tumbuhan yang banyak dijumpai di pesisir pantai Kota Singkawang. Tumbuhan ini berpotensi digunakan untuk mengobati diare. Penelitian ini bertujuan untuk mengetahui aktivitas antibakteri daun kayu putih yang berasal dariKota Singkawang terhadap bakteri uji Escherichia coli dan Staphylococcus aureus. Metode yang digunakan untuk isolasi minyak atsiri yaitu distilasi uap, sedangkan uji aktivitas antibakteri menggunakan metode difusi sumuran. Hasil isolasi minyak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Similar results were also obtained in another study the inhibition zone diameter for concentrations of 100% (14.77±0.68 mm), 75% (14.07±1.08 mm), 50% (13.23±5.30 mm), 25% (7.87±0.23 mm) [15]. In addition, another research also showed that at a concentration of 25 g/l (2.5%) the diameter of the inhibition zone was 3.44±0.34 mm and at a concentration of 50 g/µl (5%) the diameter of the inhibition zone was 4.39±0.48 mm, which further confirm the result in this study [14].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were also obtained in another study the inhibition zone diameter for concentrations of 100% (14.77±0.68 mm), 75% (14.07±1.08 mm), 50% (13.23±5.30 mm), 25% (7.87±0.23 mm) [15]. In addition, another research also showed that at a concentration of 25 g/l (2.5%) the diameter of the inhibition zone was 3.44±0.34 mm and at a concentration of 50 g/µl (5%) the diameter of the inhibition zone was 4.39±0.48 mm, which further confirm the result in this study [14].…”
Section: Discussionsupporting
confidence: 89%
“…In another study an analysis of eucalyptus oil (Melaleuca cajuputi) made in Singkawang, West Kalimantan, Indonesia. It was found that 9 bioactive compounds in eucalyptus oil (Melaleuca cajuputi), the highest concentration compound was 1,8-Cineol (71.96%) [14]. In this study 10 compound was found in eucalyptus oil (Melaleuca leucadendra), the highest concentration compound was 1,8-Cineol (72.30%) which is higher.…”
Section: Discussionmentioning
confidence: 48%